Somatostatin Receptor Type 2 (SSTR2) Internalization and Intracellular Trafficking in Pituitary GH-Secreting Adenomas: Role of Scaffold Proteins and Implications for Pharmacological Resistance - Treppiedi, D.; Peverelli, E.; Giardino, E.; Ferrante, E.; Calebiro, D.; Spada, A.; Mantovani, G. (Hormone and Metabolic Research, 2016)
Somatostatin receptor type 2 (SSTR2), together with SSTR5, represents the main target of medical treatment for growth hormone (GH)-secreting pituitary tumors, since it is expressed in most of these tumors and exerts both antiproliferative and cytostatic effects, and reduces hormone secretion, as well. However, clinical practice indicates a great variability in the frequency and entity of favorable responses of acromegalic patients to long-acting somatostatin analogues (SSAs), but the molecular mechanisms regulating this pharmacological resistance are not completely understood. So far, several potentially implied mechanisms have been suggested, including impaired expression of SSTRs, or post-receptor signal transduction alterations. More recently, new studies exploited the molecular factors involved in SSTRs intracellular trafficking regulation, this being a critical point for the modulation of the available active G-coupled receptors (GPCRs) amount at the cell surface. In this respect, the role of the scaffold proteins such as β-arrestins, and the cytoskeleton protein Filamin A (FLNA), have become of relevant importance for GH-secreting pituitary tumors. In fact, β-arrestins are linked to SSTR2 desensitization and internalization, and FLNA is able to regulate SSTR2 trafficking and stability at the plasma membrane. Therefore, the present review will summarize emerging evidence highlighting the role of β-arrestins and FLNA, as possible novel players in the modulation of agonist activated-SSTR2 receptor trafficking and response in GH-secreting pituitary tumors.
Keywords: pituitary tumors; receptor endocytosis; β-arrestins; filamin A